Does Resident Gender or Race/Ethnicity Affect Orthopaedic Surgery Case Volume During Residency Training? - Parisun Shoga, DO; Ann Van Heest, MD, FAOA; S. Elizabeth Ames, MD, FAOA; Sean O. Hogan, PhD; Eric Holmboe, MD; Mary Klingensmith, MD; Yoon Soo Park, PhD; Corey Parker, MPA; Erik Solberg, MA; Kimberly Templeton, MD, FAOA (JBJS Open Access)
Introduction:. Disparities in case volumes have been reported in some surgical specialties. The objective of this study was to evaluate whether gender or racial/ethnicity disparities exist during orthopaedic surgery residency surgical case log volume. Methods:. Accreditation Council for Graduate Medical Education Case Log Database for orthopaedic surgery residents for 9 years of cohorts graduating in academic years 2013-2014 to 2021-2022 were analyzed to compare case logs between men and women, as well as race/ethnicity, defined by Association of American Medical Colleges as underrepresented in medicine (URiM) and non-URiM groups. Results:. Longitudinal analyses of total required minimum type cases indicate significant gender differences among the initial graduating cohorts with women trainees reporting 33 cases fewer than men; in the most recent years of this study period, women trainees reported 5 cases fewer than men per year. URiM trainees reported 29 cases fewer at baseline, while in the most recent years, there were no significant differences. Significant differences exist for 8 of the 15 case minimum types with fewer women cases at baseline; in the most recent years, women had fewer cases in anterior cruciate ligament Reconstruction, Ankle Fracture Fixation, Closed Reduction Forearm Fracture, Total Hip Arthroplasty, and Total Knee Arthroplasty. There were significant differences for 3 of 15 case minimum types at baseline for URiM trainees with no significant differences in most recent years. Hand was the only anatomic area with women reporting significantly more cases than men, both initially and over the 9 years of study period. Conclusion:. Significant differences exist in case volume and case types during orthopaedic surgery residency based on gender for the initial cohort, albeit lessening in most recent years. Although initial differences in cases volumes based on race/ethnicity exist, no significant differences persist in most recent years of the study period. Level of Evidence:. Level III. See Instructions for Authors for a complete description of levels of evidence.